Caregivers’ socio-cultural influences on health-seeking behavior for their wasted children among forcibly displaced Myanmar Nationals and their nearest host communities - Naila, Nurun Nahar; Islam, Md. Munirul; Alam, Aklima; Karmakar, Gobinda; Mahfuz, Mustafa; Mostafa, Ishita; Sharmin, Farhana; Manir, Mohammad Zahidul; Sari, Mayang; Ahmed, Tahmeed; Rahman, Mahfuzur (Frontiers in Nutrition, 2023)
A total of 19% of forcibly displaced Myanmar Nationals (FDMNs) originating from Bangladesh fall within the age range of under five years old, while an average of 1% exhibit severe malnutrition. The nearest host community of FDMNs in Cox's Bazar is more conservative in culture and religion than the rest of Bangladesh and shares linguistic, ethnic, and cultural connections with FDMNs. A qualitative study was conducted to investigate the impact of socio-cultural factors on the healthcareseeking behavior of caregivers of critically malnourished children in FDMN camps and neighboring host communities. The utilization of informal healthcare providers by caregivers in both populations can be attributed to cultural attitudes, taboos, and peer pressure. The healthcare practices in the FDMN camps and host towns were primarily affected by household responsibilities, familial assistance in accessing medical services, decisions made by husbands or mothers-in-law, and the availability and accessibility of healthcare facilities. Certain features were identified that prompt caregivers to seek formal treatment in both groups. The efficacy of the treatment was a primary consideration. In instances where conventional remedies and informal treatments proved ineffective in restoring the health of children, others who were invested in their well-being, such as family members and neighbors, advised caretakers to pursue professional medical care. Enhanced caregiver awareness of severe wasting, enhanced healthcare accessibility, and increased community volunteer engagement have the potential to facilitate early identification of severely wasted children and mitigate delays in treatment.